A sociological analysis of Rhodes University Students previously diagnosed with Attention Deficit/Hyperactivity Disorder (ADHD) and prescribed psychostimulant medications - Brasher, Chelsea Marilyn (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
Using the theoretical framework of symbolic interactionism, bringing into account the labelling theory, the stigmas attached upon mental health issues and the medicalization approach, this study sought to document and analyze the viewpoints that previously diagnosed Rhodes University students hold towards the ADHD label and the subsequent usage of psychostimulant medications. Seven respondents were involved in an in-depth interviewing process. Out of the seven respondents chosen, five of the respondents were diagnosed in their primary school years, whereas the other two respondents were diagnosed in their late teenage years or early adult years. These respondents were included to enlighten and support the narrative of the five respondents diagnosed in their youth. The findings varied, with some of the respondents feeling negatively affected by having the ADHD label attached to them, and others, positively affected by it. The findings were also diverse in terms of how the respondents experienced stimulant usage, with some believing that the benefits of usage outweigh the costs, and others, the opposite. At a general level, it was discovered that the respondents were not affected by the ADHD label in terms of their interactions with others in primary school. It was only as they got older did some become fearful of the stigma attached to the ADHD label, and that of medication.
Keywords: Stereotypes (Social psychology); Mental illness -- Public opinion; Attention-deficit hyperactivity disorder; Attention-deficit hyperactivity disorder -- Treatment; Symbolic interactionism